The productivity advantages of large cities: Distinguishing agglomeration from firm selection - Pierre-Philippe Combes; Gilles Duranton; Laurent Gobillon; Diego Puga; Sébastien Roux (Institute for the Study of Labor (IZA), 2012)
Firms are more productive on average in larger cities. Two main explanations have been offered: firm selection (larger cities toughen competition, allowing only the most productive to survive) and agglomeration economies (larger cities promote interactions that increase productivity), possibly reinforced by localised natural advantage. To distinguish between them, we nest a generalised version of a tractable firm selection model and a standard model of agglomeration. Stronger selection in larger cities left-truncates the productivity distribution whereas stronger agglomeration right-shifts and dilates the distribution. Using this prediction, French establishment level data, and a new quantile approach, we show that firm selection cannot explain spatial productivity differences. This result holds across sectors, city size thresholds, establishment samples, and area definitions.
urn:nbn:de:101:1-2012080812474
Keywords: C52; R12; D24; 330; agglomeration; firm selection; productivity; cities; Produktivität; Großstadt; Agglomerationseffekt; Unternehmenserfolg; Marktaustritt; Theorie